2020
DOI: 10.2478/jvetres-2020-0071
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of gastrointestinal parasites in camels in the Tianshan Mountains pastoral area in China

Abstract: IntroductionGastrointestinal parasites are some of the most common pathogens which are seriously harmful to the camel’s health. The infection status of gastrointestinal parasites in camels (Camelus bactrianus) in the Tianshan Mountains pastoral area in China is still unclear. The aim of this study was to investigate the species and infection intensity of gastrointestinal tract parasites in local camels.Material and MethodsA total of 362 fresh faecal samples were collected and examined for parasite eggs using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
5
7
0
Order By: Relevance
“…It is clear that as the age of the camels increases, the exposure to different types of parasites is more and the prevalence of parasites might be higher as well. The present result is supported by different researchers stating that age and prevalence of GIT parasites are directly related in camels [ 9 , 11 , 14 , 19 , 22 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is clear that as the age of the camels increases, the exposure to different types of parasites is more and the prevalence of parasites might be higher as well. The present result is supported by different researchers stating that age and prevalence of GIT parasites are directly related in camels [ 9 , 11 , 14 , 19 , 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is clear that as the age of the camels increases, the exposure to different types of parasites is more and the prevalence of parasites might be higher as well. e present result is supported by different researchers stating that age and prevalence of GIT parasites are directly related in camels [9,11,14,19,22]. e prevalence of gastrointestinal parasites is higher in females (76.99%) than males (71.76%), but the difference is not statistically significant (p value >0.05).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…in young camels. Similarly, Ararsa et al (2014) and Guowu et al (2020) reported that age might be a risk factor for the high prevalent gastrointestinal parasites infectivity among camels. Other reports observed no association between age of the host and the prevalence of the parasites (Parmar et al 2019;Bouragba et al 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Gastrointestinal parasitic infection is one of the most common obstacles among the camel population worldwide (Guowu et al 2020;El-Seify et al 2021;Bouasla et al 2023).…”
Section: Introductionmentioning
confidence: 99%